Traumatic subtalar joint dislocation. (2nd February 2023) - Anazor, Fitzgerald C; Dhinsa, Baljinder S
Abstract : Although uncommon, subtalar joint dislocations remain a frequently missed orthopaedic emergency. Detailed soft tissue and neurovascular assessment is important and these should be documented as appropriate. Failure of urgent reduction might lead to increased risk of conversion to an open injury as a result of pressure necrosis of the overlying skin, risk of talar avascular necrosis and risk of neurovascular compromise. A computed tomography scan is needed in all cases following successful closed or open reduction to identify associated occult foot and ankle fractures. The goal of treatment is to reduce the risk of soft tissue and neurovascular compromise and achieve a supple, painless foot. This article highlights the importance of early identification of this injury and institution of appropriate management according to the latest evidence, to reduce the risk of complications and lead to the best outcomes.